Climate change and water resources in the Middle East: Vulnerability, socio-economic impacts, and adaption - Mutasem El- Fadel; Elie R. Bou-Zeid (Fondazione Eni Enrico Mattei (FEEM), 2001)
While the extent of human induced global warming is inconclusive, the vulnerability of natural systems to rapid changes in climate patterns is regarded as one of the most challenging issues in recent years. Water resources are a main component of natural systems that might be affected by climate change. This paper characterises water resources in several Middle Eastern countries and evaluates regional climate predictions for various scenarios using General Circulation Models. Adaptation measures are assessed with a focus on no-regret actions in the context of local socio-economic and environmental frameworks.
Keywords: Q25; 330; Climate change; water resources; water balance; Middle East; Wasser; Klimawandel; Umweltbewertung; Mittlerer Osten